The Involvement of Religious Communities in the teaching of Multi-faith Syllabus in Botswana Junior Secondary Schools - Masheko, C.; Bhicoo, A.; Dema, T.; M, Mosweu; Thekiso, T.; Mmolai, Sana Koketso (Advances in Social Sciences Research Journal, 2016)
Prior to 1996, Religious Education (RE) in Botswana junior secondary schools was Christian based and there were no significant disparities in academic performance between RE and other subjects. Since the introduction of a multi-faith syllabus there has been a decline in the academic performance in this subject. Perhaps this situation emanates from the fact that most RE teachers and students are Christians. Possibly, Christian teachers and students may not be familiar with the dimensions of other world religions explored in this syllabus. This study was therefore carried out to investigate if the involvement of religious communities could be of assistance in the teaching and learning of the multi-faith syllabus in Botswana junior secondary schools. The study used random, purposive and convenience sampling techniques to select the population from twelve (12) junior secondary schools and seven (7) religions. Data was collected from thirty-six (36) RE teachers, one hundred and twenty (120) students and fifty-six (56) representatives of the seven (7) religions prevalent in Botswana and explored in this syllabus. The study used questionnaires and interviews to collect data. The findings of this study revealed that the involvement of religious communities in the teaching and learning of multi-faith syllabus in Botswana junior secondary schools is capable of assisting in knowledge acquisition of the various religions explored in this syllabus by providing first–hand information from adherents of the explored religions. This study therefore recommends that the Ministry of Basic Education, School Management Teams and Parents and Teachers Associations should encourage the involvement of religious communities as an attempt to improve RE Junior Certificate results.